Beispiel Nr: 21
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2 x -7 y =-8\\ 7 x -1 y = -9 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 2 x -7 y =-8\\ II \qquad 7 x -1 y = -9 \\ \text{I nach y auflösen}\\ 2 x -7 y =-8 \\ 2 x -7 y =-8 \qquad /-2 x\\ -7 y =-8 -2 x \qquad /:\left(-7\right) \\ y =1\frac{1}{7} +\frac{2}{7} x \\ \text{II nach y auflösen}\\ 7 x -1 y =-9 \\ 7 x -1 y =-9 \qquad /-7 x\\ -1 y =-9 -7 x \qquad /:\left(-1\right) \\ y =9 +7 x \\ \text{I = II}\\ 1\frac{1}{7} +\frac{2}{7} x =9 +7 x \qquad /-\frac{2}{7} x /-9 \\ 1\frac{1}{7}-9 =7 x -\frac{2}{7} x \\ -7\frac{6}{7} =6\frac{5}{7} x \qquad /:6\frac{5}{7} \\ x=-1\frac{8}{47} \\ \text{x in I}\\ y =1\frac{1}{7} +\frac{2}{7} \cdot -1\frac{8}{47} \\ y=\frac{38}{47} \\ L=\{-1\frac{8}{47}/\frac{38}{47}\} \end{array} & \begin{array}{l} I \qquad 2 x -7 y =-8\\ II \qquad 7 x -1 y = -9 \\ \text{I nach x auflösen}\\ 2 x -7 y =-8 \\ 2 x -7 y =-8 \qquad /+7 y\\ 2 x =-8 +7 y \qquad /:2 \\ x =-4 +3\frac{1}{2} y \\ \text{II nach x auflösen}\\ 7 x -1 y =-9 \\ 7 x -1 y =-9 \qquad /+1 y\\ 7 x =-9 +1 y \qquad /:7 \\ x =-1\frac{2}{7} +\frac{1}{7} y \\ \text{I = II}\\ -4 +3\frac{1}{2} y =-1\frac{2}{7} +\frac{1}{7} y \qquad /-3\frac{1}{2} y /+1\frac{2}{7} \\ -4+1\frac{2}{7} =\frac{1}{7} y -3\frac{1}{2} y \\ -2\frac{5}{7} =-3\frac{5}{14} y \qquad /:\left(-3\frac{5}{14}\right) \\ y=\frac{38}{47} \\ \text{y in I}\\ x =-4 +3\frac{1}{2} \cdot \frac{38}{47} \\ x=-1\frac{8}{47} \\ L=\{-1\frac{8}{47}/\frac{38}{47}\} \end{array} \end{array} $